1989
DOI: 10.1016/0014-5793(89)81796-x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of sites on chromosomal protein HMG‐I phosphorylated by casein kinase II

Abstract: The amino acid sequence of a region on chromosomal protein HMG-I from human cells that is phosphorylated by casein kinase II has been determined. The sequence is: Leu-Glu-Lys-Glu-Glu-Glu-Glu-Gly-Ile-Ser-Gln-Glu-Ser(P)-Ser(P)-Glu-Glu-Glu-Gln.It corresponds to the C-terminal residues 90-107 of HMG-I [(1989) Mol. Cell. Biol. 9,21142123]. Sequence analysis of the native peptide (g&107) after treatment, which specifically converts phosphoserine residues to S-ethylcysteine, revealed that 7&80% of serine residues 102… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
56
2

Year Published

1990
1990
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(60 citation statements)
references
References 25 publications
2
56
2
Order By: Relevance
“…1A). This phosphorylation reflects a constitutive modification found in native forms of these proteins (53)(54)(55). The free and DNA-bound proteins were digested with hydroxyl radicals, and the digestion products were separated by electrophoresis.…”
Section: High Mobility Group Proteins Hmgi Hmgy Hmgi-c and Chmgi Imentioning
confidence: 90%
See 1 more Smart Citation
“…1A). This phosphorylation reflects a constitutive modification found in native forms of these proteins (53)(54)(55). The free and DNA-bound proteins were digested with hydroxyl radicals, and the digestion products were separated by electrophoresis.…”
Section: High Mobility Group Proteins Hmgi Hmgy Hmgi-c and Chmgi Imentioning
confidence: 90%
“…Phosphorylation Affects Contacts of HMGY with DNA-Previous studies have shown that mammalian and insect HMGI/Y proteins are in vivo phosphorylated at several positions by CK2 (53)(54)(55) and Cdc2 kinase (56 -58). In some reports, a general phosphorylation-dependent attenuation of binding affinity of the proteins has been demonstrated (56 -60); however, the mechanism of these changes was not studied.…”
Section: Fig 5 Ethylation (A) and Methylation (B) Interference Analmentioning
confidence: 99%
“…For HMGA1, it has been suggested that removal of the acidic tail has important implications for regulatory control of its binding affinity to DNA (32). This carboxyl-terminal acidic motif contains a consensus recognition sequence for casein kinase II, which phosphorylates HMGA1 in vitro and in vivo (41). Upon casein kinase II -dependent phosphorylation of HMGA1 in vivo, its affinity for DNA decreases (42).…”
Section: Discussionmentioning
confidence: 99%
“…They are phosphorylated by protein kinase CK2 (18,19) and, in a cell-cycle-and differentiation-dependent manner, by Cdc2 kinase (20 -22), mitogen-activated protein kinase, and protein kinase C (22). In vivo the entire population of the HMGI-C protein appears to be phosphorylated (23).…”
mentioning
confidence: 99%